G protein-coupled receptors : emerging paradigms in activation, signaling and regulation Part A - Shukla, Arun K. (International review of cell and molecular biology, 2018)
G Protein-Coupled Receptors: Emerging Paradigms in Activation, Signaling and Regulation, Part A, Volume 337 in the International Review of Cell and Molecular Biology series, reviews and details current advances in cell and molecular biology. The IRCMB series has a worldwide readership, maintaining a high standard by publishing invited articles on important and timely topics that are authored by prominent cell and molecular biologists.